Household water insecurity and psychological distress in Eastern Ethiopia: Unfairness and water sharing as undertheorized factors - Alexandra Brewis; Kedir Teji Roba; Amber Wutich; Mason Manning; Jemal Yousuf (Elsevier, 2021)
Elevated levels of mental health symptoms - especially related to depression and anxiety - are observed in water-insecure communities. A small set of ethnographic studies have suggested that inadequate safe and sufficient water does not in itself well explain observed patterns; rather the social contexts of water is critical. The most commonly theorized explanatory mechanism is the distress of perceived unfairness acting as a psychosocial stressor, although direct empirical tests of this are currently lacking. Another theorized and untested mechanism is the stress of social interactions around household water (like participation with neighbors in water sharing systems). Based on a sample of N ​= ​1543 women ages 18-49 years (all with young children in the home) collected in Eastern Hararghe, Oromia, Eastern Ethiopia from June to September 2019, we tested the effects of two theorized mechanisms potentially implicated in why water causes psychosocial distress: perceived unfairness in the water system and level of participation in informal water sharing systems. In these predominantly smallholder agricultural households, and taking into account expected covariates like role-responsibility for water and household food insecurity, we find that perceived unfairness accounted for two-thirds of the effect of household water insecurity on individual depression/anxiety symptom levels. Even taking all these factors into account, high (and assumably predictable) levels of participation in water borrowing were associated with better mental health. However, less frequent (and assumably less predictable) borrowing was associated with worse outcomes. Together these findings provide needed empirical support for the propositions that the negative mental health effects of water insecurity are fundamentally tied to the dynamic social mechanisms around and meanings of water in water insecure communities, much more so than water access in itself.